Labor economics - Borjas, George J. (New York: Mcgraw Hill, 2024)
"The book also makes extensive use of labor market statistics and reports evidence obtained from hundreds of research studies. These data summarize the stylized facts that a good theory of the labor market should be able to explain, as well as help shape our thinking about the way the labor market works. The main objective of the book, therefore, is to survey the field of labor economics with an emphasis on both theory and facts. The book relies much more heavily on "the economic way of thinking" than competing textbooks. I believe this approach gives a much better understanding of labor economics than an approach that minimizes or ignores the story-telling aspects of economic theory"--
Includes bibliographical references and index.
Keywords: Labor economics; Labor market -- United States